STRUCTURE OF CORAL COMMUNITY IN SIDODADI VILLAGE, TELUK PANDAN DISTRICT, PESAWARAN REGENCY - Kusuma, Anma Hari (Jurnal Perikanan Unram, 2025)
Indonesian waters have abundant natural resources, one of which is coral reefs. The purpose of this study was to analyze the structure of the coral community in Sidodadi Village, Pesawaran Regency. The research was conducted in September 2023. The research location was in the waters of Sidodadi Village, Teluk Pandan District, Pesawaran Regency, Lampung Province. The research method used Underwater Photo Transect (UPT). Data analysis with CPCe software. The percentage of live coral cover in the observation area at station 1 was 44,65%, station 2 was 0,12%, station 3 was 78,03% and station 4 was 44,05%. The category of coral cover percentage was very good, moderate and poor. The physicochemical conditions of the waters were classified as good to support coral growth. The diversity index value at the research location was included in the low category, the uniformity index value was included in the low and high categories and the dominance index value was included in the low and high categories. The physicochemical parameters of the waters that most influenced the amount of coral cover were dissolved oxygen and brightness.